Interplanting Different Varieties of a Sweet Potato Crop to Reduce Damage by Oligophagous Insect Pests. (31st January 2019) - Ichinose, K; Reddy, G V P; Shrestha, G; Sharma, A; Okada, Y; Yoshida, M; Sakai, Tetsufumi
Abstract: One complementary or alternative control measure to chemical insecticide is interplanting of plants that affect insect behavior. While few successes are known based on interplanting of different varieties of the same crop, such intra-crop interplanting may be effective against insects that feed on a limited range of plants and have persistent preference to one cultivar. Here, we report three field trials that examined the efficacy of intra-crop interplanting of sweet potato varieties, Ipomoea batatas (L.) Lamarck (Solanales: Convolvulaceae), on an oligophagous weevil, Euscepes postfasciatus (Fairmaire) (Coleoptera: Curculionidae), planting a preferred variety, Beni-masari, together with a less preferred one, Kyushu 166. In the first experiment, Beni-masari was planted as a border around Kyushu 166 and this arrangement decreased tuber damage in the main crop (Kyushu 166), although damage reduction was not statistically significant from monoculture plantings of Kyushu 166. In the second experiment, both varieties were planted in plots spaced 3 m apart to test the attractiveness of Beni-masari to weevils from Kyushu 166. No attractive effects of Beni-masari were observed. In the third experiment, the two varieties were planted in separate plots that were contiguous to each other, and in this experiment Beni-masari preferentially attracted weevils away from Kyushu 166 within 3 m distance, and tuber damage in Kyushu 166 within that zone was reduced owing to the attractiveness of Beni-masari. We discuss the potential of the intra-crop interplanting in pest management.